2022
DOI: 10.1021/acs.orglett.2c03232
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Mediated Redox Cyclization of 1-(2-Nitroaryl)prop-2-ynones to 3-Hydroxyquinolin-4-ones: Formal Intramolecular Oxyamination of α,β-Ynones

Abstract: 3-Hydroxyquinoline-4(1H)-ones (3HQs) are privileged structural motifs. The current methods for their synthesis necessitate strongly acidic or basic conditions, which hamper the generality and practicality. Here, we describe phosphine-mediated redox transformation of easily accessible 1-(2nitroaryl)prop-2-ynones to 3HQs. Besides establishing a new entry to the synthesis of 3HQs under neutral conditions, this method is the first formal intramolecular oxyamination of α,β-ynones. The synthetic utility of this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Recently, the phosphine-mediated redox reaction of 1-(2-nitroaryl)prop-2-ynones to access a wide range of 3-hydroxyquinoline-4(1 H )-ones 82 (3HQs) was reported by the group of Ramasastry (Scheme 37). 66 The reaction scope is broad. The authors reported that the Michael addition of phosphines to 81 would generate intermediate I .…”
Section: Synthesis Of 6-membered N-heterocyclesmentioning
confidence: 99%
“…Recently, the phosphine-mediated redox reaction of 1-(2-nitroaryl)prop-2-ynones to access a wide range of 3-hydroxyquinoline-4(1 H )-ones 82 (3HQs) was reported by the group of Ramasastry (Scheme 37). 66 The reaction scope is broad. The authors reported that the Michael addition of phosphines to 81 would generate intermediate I .…”
Section: Synthesis Of 6-membered N-heterocyclesmentioning
confidence: 99%
“…The reaction could initially involve an addition of PPh 3 to the alkyne part, which subsequently triggered an intramolecular cyclization of 1a to form organic phosphonium A . 17 Subsequent cleavage of the N–O bond of species A and isomerization led to the formation of phosphorus ylide B , which was then followed by a Wittig-like cyclization to give the intermediate C . Next, deoxygenation of C led to the formation of intermediate D and Ph 3 PO (as side product).…”
Section: Resultsmentioning
confidence: 99%
“…With the experience in the α,β-ynone chemistry, we considered a new substrate design: nitro-ynones 36 , Scheme 16. 50 Based on related literature reports, 51 we envisioned that the 1,4-addition of phosphine to 36 generates allenolates AE , which could be trapped by the nitro group to form zwitterionic intermediates AF . It was expected that AF would reorganise to form the ylides AG that could undergo intramolecular Wittig-type deoxygenation to generate iminoketones 38 .…”
Section: Phosphine-mediated Transformations Of Activated Alkynesmentioning
confidence: 99%